Comparative analysis of quality and safety indicators of “Adygeyskiy” dry cheese and “Parmesan” hard cheese - Z. N. Khatko; M. A. Gasheva; A. B. Tkhaishaova; N. S. Khishtova; Y. E. Saprykina (Новые технологии, 2018)
The article presents the results of research on the quality and safety of four cheese samples. It has been established that “Adygeyskiy” dry cheese has high quality and safety indicators despite the maturity dates, does not contain plant raw materials and GMO, unlike two samples of foreign cheese (Parmesan Dolce Granto, Uruguay, Parmigiano Regano, Italy).